Upaya Jepang dalam Melindungi Hak atas Kekayaan Intelektual Industri Anime dan Manga - Widhi Prasetia Nugraha; Hermini Susiatiningsih (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
Anime and manga have been objects to digital copyright infringement by its fans around the globe for years. Fansubbing and scanlation activities creates a huge economic loss for Japan every year. In an effort to protect the intellectual property rights of anime and manga, Japan’s Ministry of Economy, Trade, and Industry in collaboration with anime and manga publishers are starting the Manga Anime Guardian Project. The purpose of this research is to explain how the project used to protect the intellectual property rights of anime and manga. Using liberalism view of the property right and the concept of public policy, this study argues that it is Japan’s responsibility to protect anime and manga as it’s people economy product, and cooperation between goverment and publishers is essential to implement policy strategies. The results of this study indicate that cooperative efforts of intellectual property right protection is done by persuasive approach to the fans and begin to bans sites that listed as illegal sites sharing intellectual property products protected under Berne Convention of Intellectual Property Rights.